Coexpression of anticipatory and consummatory volitional deficits in schizophrenia and their association with memory impairment - Lam Joyce; Ng Fung Hoi Marcus; Cheng Ivy Yee Po; Välimäki Maritta; Yee K. Benjamin (American Psychological Association, 2025)
Avolition in schizophrenia has been attributed to the decoupling between emotion and motivation rather than an inability to perceive or distinguish emotions. Hence, goal-directed behavior incentivized by positive or negative reinforcement becomes impoverished and dull. It is further suggested that goal-directed actions directed at future outcomes (anticipatory or representational response) are preferentially affected, as opposed to actions directed to the current state of affairs (consummatory or evoked response). Attempts to dissociate them behaviorally using the “anticipatory and consummatory pleasure” (ACP) task have demonstrated deficits in both components, yet some have claimed otherwise. In this replication study, we presented further characterization of the pronounced deficits in valence-dependent consummatory as well as anticipatory responding in 40 subjects with schizophrenia in comparison with 42 healthy subjects. In addition, two novel observations were made. First, the correlation between ratings of emotional intensity and arousal levels of pictures used to motivate responding in the ACP task was markedly attenuated in the schizophrenic (SZ) group, suggesting that the decoupling from emotion may be manifested beyond goal-directed behavior in schizophrenia. Second, multiple correlations between ACP performance indices and individual scores in the letter–number span test were uniquely observed in the SZ group, not among healthy controls. The co-emergence of ACP and working memory deficiency in SZ may be linked to common psychopathological processes